Kebijakan Visa Indonesia: Keamanan, Dampak, Peluang, Tantangan dan Teknologi Informasi - Anshari, Afif Nur; Noviarini, Nurina; Chandra, Luqman Nur; Mayline, Hardika; Ariani S, Atika (UI Scholars Hub, 2022)
A visa is an authorization for an individual to travel to the country issuing the visa before get a residence permit. Given the importance of the visa function for the State in controlling and supervising the entry and stay of foreigners to enter the territory of a country, it is deemed necessary to further elaborate on visa policies in Indonesia. This research uses a qualitative approach which is research that aims to observe, investigate and describe the development of visas in Indonesia so that it can be found in the field how the development of visas in Indonesia both in terms of state security, impacts and opportunities as well as challenges that can occur as well as the use of information technology in support the visa policy and see best practices in visa policies in other countries as an overview and input for the development of visa policies in Indonesia. Keywords: Visa Policy, State Control, State Security, Information Technology